Coordinated Androgen and Estrogen-receptor microRNA 26 Directive in Breast and Prostate Tumour - Fattepur, Santosh; Nilugal, Kiran Chanabasappa; Abdullah, Ibrahim; Sreeharsha, Nagaraja; Anwer, Md. Khalid; Asdaq, Syed Mohammed Basheeruddin (Indian Journal of Pharmaceutical Education and Research, 2021)
MiR-26 is a miRNA tumour suppressor that is frequently dysregulated in many tumour tissues and lines of tumour cells. Androgen and Estrogen receptor (AR & ER) were evolving as a target to examine among hormone proteins since it appears to show a part at numerous phases of growth of breast and prostate cancers. For that kind of reason, AR and ER are becoming very relevant in recent times. Although its position remains problematic in medical care, the various finding had demonstrated a link among microRNAs 26, a group of receptors of genetic expression, and cancer (AR & ER), but there is still little evidence for the association among BC and PC miRNAs. The major goal of our study is to deliver AR and ER pathways involved in the development of microRNAs 26. Moreover, the functional and structural analysis of microRNAs 26 concerning cancer and non-cancerous cells were also discussed briefly. Additionally, the gene for post-transcriptional regulatory functions in breast and prostate cancer of different dysfunctional miRNAs 26 and their medicinal properties were also presented.
Keywords: Breast cancer; Prostate cancer; microRNA 26; Androgen receptor (AR); Estrogen receptor (ER)